Corrigendum - Putignano S (Dove Medical Press, 2012)
Putignano S, Gareri P, Castagna A, Cerqua G, Cervera P, Cotroneo AM, Fiorillo F, Grella R, Lacava R, Maddonni A, Marino S, Pluderi A, Putignano D, Rocca F. Retrospective and observational study to assess the efficacy of citicoline in elderly patients suffering from stupor related to complex geriatric syndrome. Clin Interv Aging. 2012;7:113–118.One of the author’s names was listed incorrectly as Roberto Grella, it should have been Rodolfo Grella.Read the original article